Brain-gut miscommunication biopsychosocial predictors of quality of life in irritable bowel syndrome - Pletikosić, Sanda; Tkalčić, Mladenka; Hauser, Goran (2018)
Irritable bowel syndrome (IBS) is a complex disorder that results from interactions of numerous factors. The biopsychosocial model describes a number of predisposing, precipitating, and perpetuating factors, which contribute to the onset and maintenance of symptoms and consequently to quality of life (QoL) impairment. The aim of this study was to examine the impact of several psychological and biological factors on the physical and mental components of QoL in IBS patients. A total of 46 IBS patients completed a set of questionnaires (Big Five Inventory, State-Trait Anxiety Inventory, Beck Depression Inventory-II, Medical Outcome Study Short-Form 36) and kept a diary of their mood, daily stress, and symptoms over a period of two weeks. Patients' heart rate variability, serum cortisol, and fecal calprotectin levels were also measured. The results of regression analyses showed that depression (β = -.30) and negative mood (β = -.28) predicted physical QoL, while depression (β = -.45) and positive mood (β = .33) significantly predicted mental QoL. The model, which included calprotectin, cortisol, anxiety, depression, and positive and negative mood, explained a total of 47% of variance of physical and 57% of variance of mental QoL. Our results confirm the role of negative affect in IBS QoL impairment. They also indicate that biological factors seem important for physical QoL in IBS patients. The role of positive mood as a protective factor for mental QoL might be significant for psychological interventions with IBS patients.
El síndrome del intestino irritable (SII) es un trastorno complejo, resultado de la interacción de numerosos factores. El modelo biopsicosocial describe algunos factores de predisposición, precipitación y perpetuación que contribuyen a la apariencia y mantenimiento de síntomas, y por consiguiente, al deterioro de la calidad de vida. El objetivo de este trabajo fue examinar el efecto que tienen ciertos factores psicológicos y biológicos sobre los componentes de la calidad de vida en los pacientes que sufren SII. Un total de 46 pacientes con SII completaron un conjunto de cuestionarios (Inventario de Los Cinco Grandes, Inventario de Ansiedad Estado-Rasgo, Inventario de Depresión de Beck II, Cuestionario de Salud SF-36) y durante dos semanas escribían un diario sobre su estado de ánimo, estrés diario y síntomas. Además, se midió su variabilidad del ritmo cardíaco, cortisol sérico y niveles de calprotectina fecal. Los resultados del análisis regresiva mostraron que la depresión (β = -.30) y mal humor (β = -.28) predijeron calidad de vida física, mientras que la depresión (β = -.45) y buen humor (β = -.33) predijeron significativamente calidad de vida mental. El modelo, que incluyó calprotectina, cortisol, ansiedad, depresión y buen y mal humor, explicó el 47% de la varianza de la calidad de vida física y el 57% de la calidad de vida mental. Nuestros resultados confirmaron el papel del afecto negativo en el deterioro de la calidad de vida en el SII. También indicaron que los factores biológicos parecen importantes para la calidad de vida física en los pacientes con SII. El papel del buen humor como un factor protector para la calidad de vida mental podría ser significativo para las intervenciones psicológicas en los pacientes con SII.
Bibliografija: str. 107-114.
Resumen
Keywords: Sindrom iritabilnog crijeva -- Biopsihosocijalni model -- Kvaliteta života -- Depresija -- Raspoloženje